Zahraniční politika Francie vůči Africe po zvolení Emmanuela Macrona - Šmejkalová, Martina; Druláková, Radka, 1973-; Šabacká, Yvona, 1977-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2020)
The aim of this bachelor thesis is to ascertain to what extent is Emmanuel Macron's vision of economic assistance to Africa accomplished. This thesis is focused on supporting the private sector, which significantly contributes to positive economic growth and employment in Africa. This support is linked to a further commitment to increase ODA (Official development assistance) levels to 0.55% of GNI by 2022.
Vedoucí práce: Radka Druláková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: mezinárodní studia - diplomacie [obor bakal. práce]; bakalářské práce; bachelor's theses